Exploratory Analysis Affecting Self-Efficacy in the Leadership of Female Village Heads : Analisis Eksploratori yang Mempengaruhi Efikasi Diri pada Kepemimpinan Kepala Desa Perempuan - Sri Susilawati Wati; Rita Ambarwati Sukmono (Academia Open, 2021)
Leadership is one of the most decisive factors in the development and progress of an organization. With a capable leadership that will have an impact on the progress of the organization. Public leadership by women has less legitimacy by society. Self-leadership has a significant effect on self-efficacy, self-efficacy has a significant effect on performance, self-leadership has a significant effect on performance. In order to optimize the ability of women's public leadership, self-efficacy in leadership by female headman indirectly affects the quality of leadership and service to the community. This study aims to explore the self-efficacy of female headman in the region and identify factors that influence the self-efficacy of female headman when in office as village government. This research was conducted through a self-administered questionnaire. In addition, exploration and confirmation of factor analysis were carried out. The validity and reliability tests were carried out before using exploratory factor analysis (EFA). The results of the factoring will show the communalities table, and after the rotation, a loading factor will be formed which will show the interpretation of the factors that have been formed, in particular giving names to the factors that are considered to represent these indicators. The results showed that 2 factors were formed which influenced the self-efficacy of female headman in leading village officials. These factors are Leadership Self Efficacy and Development of the Leadership Self-efficacy. The factor 1 is namely Leadership Self Efficacy which includes leading change, delegating tasks, influencing members, being flexible. Factor 2, namely Development of the Leadership Self-efficacy which includes self-identification, motivating members, leading the organization, and encouraging the organization.